Implementation of The Provincial Government’s Authority to Carry Out Sister Province Cooperation In The Perspective of International and National Law Case Study: Sister Province Cooperationbetween Province of NTB And Northern Province of Australia - Amar Tyanto; Muh Risnain; Diva Pitaloka (Mataram Journal of International Law, 2023)
The purpose of this study is to examine and analyze the position and strength of the LoI between the West Nusa Tenggara Provincial Government and the Northern Territory Government regarding sister province cooperation from the perspective of international law and national law. Furthermore, this research also examines the implementation of government authority and dispute resolution mechanisms stipulated in the Letter of Interest in the context of Sister Province agreements according to international law. The research method used is normative empirical. The Letter of Intent (LoI) between the West Nusa Tenggara Provincial Government and the Northern Territory Government regarding sister province cooperation has limited power and does not have binding legal force in the perspective of international law and national law. However, in the implementation of the authority exercised, the West Nusa Tenggara Provincial Government and the Northern Territory Government have gone through the stages of exploration, formulation of texts, and negotiations. The mechanism for resolving differences as stipulated in Article 10 requires an amicable settlement of any differences arising from the interpretation or implementation of the contents of the agreement.